2019
DOI: 10.1177/2043808719834451
|View full text |Cite
|
Sign up to set email alerts
|

Out with the old and in with the new: The role of intolerance of uncertainty in reversal of threat and safety

Abstract: Intolerance of uncertainty (IU) is associated with difficulty in updating contingencies from threatening to safe during extinction learning. However, it is unknown whether high IU individuals have difficulty (1) generally with updating threat to safe associations when contingencies change or (2) specifically with updating threat to safe associations during extinction learning, where direct threat is omitted. To address this question, we recorded IU, expectancy ratings, and skin conductance in 44 healthy partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…For this purpose, we also provided participants with contingency reversal instructions after the acquisition phase. As observed in previous studies (e.g., Atlas et al, 2016;Morriss, Saldarini, Chapman, Pollard, & van Reekum, 2019;Wilson, 1968), we expected that these contingency instructions would reverse conditioned psychophysiological responses.…”
Section: Contingency Instructionsmentioning
confidence: 66%
“…For this purpose, we also provided participants with contingency reversal instructions after the acquisition phase. As observed in previous studies (e.g., Atlas et al, 2016;Morriss, Saldarini, Chapman, Pollard, & van Reekum, 2019;Wilson, 1968), we expected that these contingency instructions would reverse conditioned psychophysiological responses.…”
Section: Contingency Instructionsmentioning
confidence: 66%
“…To target trait anxiety-related processes, we suggest the subliminal induction of a threat to trigger a generalized fear state typically associated with high trait anxiety (e.g., Van Den Hout et al, 1995;Li et al, 2007;Reuman et al, 2015). This can either be achieved by a threat of shock paradigm (Clark et al, 2012;Morriss et al, 2019) or by emotional priming (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…118,152,155 ). A substantial number of studies have reported no association between trait anxiety and fear acquisition measured by self-report ratings 135,[156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172] and psychophysiological measures [159][160][161][162][163][164][165]167,170,[173][174][175][176][177][178] . Other studies found that trait anxiety modulates fear acquisition.…”
Section: Fear Acquisitionmentioning
confidence: 99%